Deskripsi Kemampuan Bahasa Ekspresif Anak Usia 4-5 Tahun Di TK Al-Ikhlas Soguo - Balowa, Cindy Cendriani; Sutisna, Icam; Laiya, Sri Wahyuningsi (Student Journal of Early Childhood Education, 2023)
The purpose of this study was to describe the expressive language skills of children aged 4-5 years at Al-Ikhlas Soguo Kindergarten, Bolaang Uki District, South Bolaang Mongondow Regency. The research method used in this research is descriptive qualitative involving 15 children as a sample. Data collection techniques used in the form of observation, interviews, and documentation. the data analysis technique used is the interactive model by Milles & Hubberman. The results obtained show that children's expressive language skills focus on the ability to express wishes, ideas and interests, participate in conversations, say simple sentences and use question words. However, in showing expressive language, children still need more time.